Prokaryotic carbon utilization in the dark ocean: Growth efficiency, leucine-to-carbon conversion factors, and their relation - Baltar, Federico; Aristegui, Javier; Gasol, Josep M.; Herndl, Gerhard J. (Aquatic Microbial Ecology, 2010)
Experiments were conducted in the mesopelagic subtropical northeast Atlantic Ocean to determine the range of variability in the prokaryotic leucine-to-carbon conversion factor (CF), and prokaryotic growth efficiency (PGE). The way prokaryotic heterotrophic production (PHP) is calculated directly influences PGE (variations of PGE between 1 and 31% were found for a single sample). The empirically obtained deep-water CFs showed a 7-fold variability (0.13 to 0.85 kg C mol–1 Leu), but were always lower than the theoretical CF of 1.55 kg C mol–1 Leu assuming no isotope dilution. Empirically determined CFs were highly correlated to PGE, suggesting that both parameters are representations of the same basic metabolic processes. Overall, the PGEs obtained in this study suggest that mesopelagic prokaryotic assemblages can sometimes be as important in carbon processing as their epipelagic counterparts 232 227 2,089 Q1 SCIE